Advances Toward a Lightweight, Variable Fidelity Wake Simulation Tool. Issue 5 (September 2020) - Saverin, Joseph; Marten, D; Nayeri, N; Paschereit, CO
Abstract: A method is presented which aims to bridge the gap between overly simplified momentum-based wake models and overly demanding finite volume models of wind turbine wake evolution. The method has been developed to allow an essentially user-defined resolution of the wake. Beyond this, all dominant field quantities are automatically resolved by the solver including convection velocity, shear stress and turbulence intensity. Two distinct methods of solution are presented which both have strengths and weaknesses, the choice of which model being fidelity and application dependent. Both methods make use of multilevel spatial integration to allow greatly improved computational efficiency. The method is here presented for 2D flow in the symmetry plane of a vertical axis wind turbine as an initial demonstration of the potential of the method.